Frequency of Metabolic Syndrome among Stroke Patients - Kabir, Ahmedul; Sadeka, MM; Ahmed, MJ; Kabir, E; Kahhar, MA (Journal of Medicine, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Background: Metabolic syndrome is a cluster of cardiovascular risk factor and is strongly associated with CVD. This study had been carried out at Mitford Hospital with a view to get a profile of the stroke patients and to obtain the proportion of the patients having metabolic syndrome. Patients & methods: In the observational study a total of fifty patients of stroke (confirmed by CT Scan) were studied at medical unit of Mitford hospital from December, 2005 to April, 2006. Results: Among the fifty stroke patients, about half (48%) were diagnosed as metabolic syndrome and there was slight female preponderance among them. Majority of the patients (79%) were from middle socio-economic class. Investigations regarding hypertension, diabetes mellitus and dyslipidaemia revealed the percentages of these risk factors along with gender distributions among the patients with stroke. Conclusion: Stage two hypertension and diabetes were the major risk factors causing stroke. This study would provide baseline line information for the future researcher in the relevant field. Â  DOI = 10.3329/jom.v9i1.1424 J MEDICINE 2008; 9 : 37-41